FALSAFAH HIDUP DALAM KONSEP KOSMOLOGI TRI HITA KARANA - I Wayan Padet; Ida Bagus Wika Krishna (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
Tri Hita Karana is a Philosophy of life,has a concept that can preserve the culturaland environmentaldiversity amid globalizastion and homoginisasi lacing.Basically Tri Hita Karana emphasize the three relationships in this life is a relationship with fellow humans being,the relationship with the surrounding nature and relationship with divinity interrelated with each other. The essence of Tri Hita Karana fundamental implies three causes of well-being that comes on the harmonious relationship between human and God,human and nature and human environment with other cultivate Tri Hita Karana will be able to wife out the views that encourage consumerism,srife and turmoil. In addition Balinesse society teaches uphold the concept of Tri Hita Karana (concept teachings in Hinduism) and implementasi in daily life.Tri Hita Karana means three and the causes of happiness means to achieve balance and harmony. Tri Hita Karana which consist of : Parhyangan is a balanced relationship between man and God Almighty,Pawongan means a harmonious relationships Between humans and other humans and palemahan means harmonious relationship between human and the natural environment as a work of art photography exploration. Tri Hita Karana is a concept visually very menumental and are valuable,jets of very high aesthetic value,provide a very strong attraction for the artists to raise it as a source of inspiration in the process its creation.Tri Hita Karana Bali as a sourceof ideas for the creation of works of art is very unique ceremonies and aesthetic with full variation found in each of the ceremonies in Bali